Differences in the Number and Karyotypes of Chromosomes of the Anura Order in Indonesia - Khairati, Ikmanisa; Razak, Abdul (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2024)
The diversity of an organism can be studied down to the cellular level. Cytological data related to certain organisms obtained can be used as information to classify these organisms. One of them is by examining the number and karyotypes owned by organisms. A karyotype is a chromosomal phenotype that includes its structural description. The purpose of this study is to see the difference in the number and karyotype of chromosomes in species belonging to the order Anura in Indonesia. The method used is a literature study of various studies related to chromosomes of species belonging to the order Anura. Based on the results of the analysis, there are differences in the number and karyotype of several species classified in the order Anura. The species of the order Anura studied in this study are Rana rufipes, Rana parvaccola, Huia sumatrana, Fejervarya limnocharis, Limnonectes cf. grunniens, Limnonectes cf. modestus, Fejervarya cancrivora, Limnonectes blythii, Polypedates celebensis, Polypedates leucomystax, Microhyla pulchra, which belongs to the families Ranidae, Dicroglossidae, Rhacophoridae, and Microhylidae. The variation in the number of diploid chromosomes of the organism studied was in the range of 22-26 chromosomes. In addition to the number of chromosomes, there are also differences in chromosomal karyotypes in each organism